2021
DOI: 10.1161/jaha.120.019140
|View full text |Cite
|
Sign up to set email alerts
|

Small Dense Low‐Density Lipoprotein Cholesterol Is the Most Atherogenic Lipoprotein Parameter in the Prospective Framingham Offspring Study

Abstract: Background Elevated plasma levels of direct low‐density lipoprotein cholesterol (LDL‐C), small dense LDL‐C (sdLDL‐C), low‐density lipoprotein (LDL) triglycerides, triglycerides, triglyceride‐rich lipoprotein cholesterol, remnant lipoprotein particle cholesterol, and lipoprotein(a) have all been associated with incident atherosclerotic cardiovascular disease (ASCVD). Our goal was to assess which parameters were most strongly associated with ASCVD risk. Methods and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 45 publications
3
66
0
2
Order By: Relevance
“…LDL consists of multiple subclasses that differ in size, density, lipid, and apolipoprotein composition, metabolic behaviour, and correlation with CV risk. The predominance of small and dense LDL particles, the so-called LDL phenotype B, is reported in lipid disorders, obesity, and type 2 diabetes, and is considered a relevant risk factor for atherogenesis and coronary heart disease [48][49][50]. Oxidized lipoproteins, both LDLox and HDLox, have atherogenic properties [51].…”
Section: Assessment Of Other Lipoprotein-related Atherogenic Biomarkersmentioning
confidence: 99%
“…LDL consists of multiple subclasses that differ in size, density, lipid, and apolipoprotein composition, metabolic behaviour, and correlation with CV risk. The predominance of small and dense LDL particles, the so-called LDL phenotype B, is reported in lipid disorders, obesity, and type 2 diabetes, and is considered a relevant risk factor for atherogenesis and coronary heart disease [48][49][50]. Oxidized lipoproteins, both LDLox and HDLox, have atherogenic properties [51].…”
Section: Assessment Of Other Lipoprotein-related Atherogenic Biomarkersmentioning
confidence: 99%
“…Both LDL and HDL are heterogeneous in nature, including various subfractions depending on the isolation method, with up to 7 and up to 10 distinct different subspecies for LDL and HDL, respectively [ 4 ]. The predominance of sdLDL has been shown over the years to be an important and independent predictor of cardiovascular events and progression of coronary heart disease, even independently of LDL-cholesterol concentrations [ 3 , 4 , 95 ]. Therefore, it has become evident that the quality rather than only the quantity of LDL is closely related to cardiovascular risk, and estimating sdLDL in clinical practice helps to identify patients at higher risk of future cardiovascular events and helps to direct specific preventive measures [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies also validated that sd-LDL is more atherogenic due to its higher degree of penetration of the arterial wall, long plasma halflife, lesser binding affinity for LDL-R and reduced resistance to oxidative stress when related with large buoyant LDL [59,36]. Since, sd-LDL particles have low antioxidant content and cholesterol level, and increased PUFA and apoB content, they are known to be more prone to lipooxidative modification [66,67]. Toft-Petersen et al [68] demonstrated that the quantity of sd-LDL was a robust univariate analyst of substantial coronary artery stenosis evaluated by both coronary angiography and non-invasive CT scanning methods.…”
Section: Fig 1 Schematic Demonstration Of Sd-ldl and Ldl Infiltration Into Endothelial Bed Followed By Plaque Formation Via Macrophages Tmentioning
confidence: 89%